LIABILITY FOR DAMAGE DUE TO OMISSION TO PERFORM HAIL STORM PROTECTION - Arsenijević, Bojana (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2022)
In this paper, the author analyzes the liability for damage to property caused by hailstorms. Although a hailstorm is a natural phenomenon, the damage caused by hail in certain situations does not represent a casus sentit dominus. The Hydrometeorological Institute of Serbia (HIS) has the exclusive authority to carry out hail suppression processes (by seeding hail-bearing clouds with silver iodide) in order to control hail growth and to reduce damage caused by hail. The issue of liability for damage caused by hail arises in case the HIS fails to perform its activities. The author focuses on cases of damage caused by hailstorms where the compensation for damage is attainable. The lack of comprehensive scientific considerations on this subject matter has generated quite a few dilemmas in judicial practice. The most important ones refer to determining the responsible person and to the legal ground of legal persons’ liability.
Keywords: liability of legal persons; hailstorms; damage caused by natural disasters; legal grounds for liability